Electro-anatomical computational cardiology in humans and experimental animal models - Sanjay R. Kharche; Randa Mudathir; C.W. McIntyre (Elsevier, 2022)
Background: A significant proportion of the world population suffer from cardiac arrythmia that lead to arrest, sudden cardiac death, and often a severely reduced quality of life post treatment. Interdisciplinary research that aims to develop novel and effective pharmaco-surgical treatments is designed to do so by providing an understanding of the arrythmia's electro-anatomical mechanisms. Experimental and computational sciences are two pillars of basic science research where animal models are often used to investigate molecule to organ multi-scale mechanisms that may translate to human. Complementary to the resource intensive experimental approach, computational cardiology offers a highly malleable methodology that integrates the dispersed experimental knowledge into unified electro-anatomical models that are now routinely used to uncover mechanistic relationships between pharmacological targets such as sub-cellular ion channels or anatomical dysfunction such as fibrotic scarring, and observables such as electrical propagation and ECG in the organ. Nonetheless, the translation of knowledge gained from small animal studies to human remains limited. At all spatio-temporal scales, anatomy is known to play a key role while impacting treatment efficacy. Purpose and methods: In this work, a pertinent review of some of the electro-anatomical computational cardiology instruments that allow the study of arrythmia in humans, rabbits (medium size), and mouse (small) is presented. Action potential generating cardiomyocyte computational models are presented. Further, electro-anatomical models as prime instruments for personalization are reviewed. Finally, some of the extant applications as well as limitations of the multi-scale computational modelling are presented. Conclusion and outcome of the review: This work brings together relevant research instruments required to undertake computational cardiology electro-anatomy investigations.